2004
DOI: 10.1093/jae/13.2.199
|View full text |Cite
|
Sign up to set email alerts
|

African Regional Agreements: Impact on Trade with or without Currency Unions

Abstract: The aim of this paper is (i) to assess the impact of regional agreements on members' trade in SubSaharan Africa (intra-regional trade as well as trade with the rest of the world), controlling for the other traditional determinants, including geography and transport costs and (ii) to compare the respective effect of the preferential trade agreements and the monetary unions. Considering the period 1962-1996, we first assess the average impact of each regional agreement on their implementation period and second w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…However, it omits a significant amount of unexplained variation in trade (Head, 2003). As a consequence, many works (including Rose, 2001;Frankel & Rose, 2002;Glick & Rose, 2002;Rose & Engel, 2002;Wilson, 2002Carrere, 2004;Njinkeu et al, 2008) 'augmented' the traditional gravity model. Traditional variables for augmentation generally include income per capita, adjacency, common language or colonial ties, border effects and membership of regional integration arrangements (Head, 2003).…”
Section: The Basic Modelmentioning
confidence: 99%
“…However, it omits a significant amount of unexplained variation in trade (Head, 2003). As a consequence, many works (including Rose, 2001;Frankel & Rose, 2002;Glick & Rose, 2002;Rose & Engel, 2002;Wilson, 2002Carrere, 2004;Njinkeu et al, 2008) 'augmented' the traditional gravity model. Traditional variables for augmentation generally include income per capita, adjacency, common language or colonial ties, border effects and membership of regional integration arrangements (Head, 2003).…”
Section: The Basic Modelmentioning
confidence: 99%
“…27 The low figures for intra-trade in CFA monetary unions seem to go against empirical findings that currency unions have a large positive effect on international trade (see, e.g., Rose, 2000). However, Carrère (2004) and Masson and Pattillo (2004b) note that trade within CFA monetary unions are around three times higher than trade between African countries with own currencies.…”
Section: Trade Integrationmentioning
confidence: 95%
“…Some studies have found a positive correlation between regional economic integration and exports performance (Ajayi, 2005;Carrère, 2004;Musila, 2005 Carrère (2004) used the Hausman-Taylor (1981) approach and showed that African regional trade agreements generated significant exports growth between member countries. For the particular case of the Franc zone, the study revealed that monetary unions (UEMOA and CEMAC) had largely reinforced the positive effect of the preferential trade agreements on intra-regional exports.…”
Section: Empirical Evidencementioning
confidence: 99%